2014
DOI: 10.3390/genes5010108
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Base Substitution Mutagenesis in Cancer Genomes

Abstract: Cancer genome sequence data provide an invaluable resource for inferring the key mechanisms by which mutations arise in cancer cells, favoring their survival, proliferation and invasiveness. Here we examine recent advances in understanding the molecular mechanisms responsible for the predominant type of genetic alteration found in cancer cells, somatic single base substitutions (SBSs). Cytosine methylation, demethylation and deamination, charge transfer reactions in DNA, DNA replication timing, chromatin statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 214 publications
(292 reference statements)
0
55
0
Order By: Relevance
“…Highly mutagenic 8-oxo-7,8 dihydroguanine (8-oxoG) could be the reason for such a bias, however other products of reactions of guanine and cytosine could also contribute 94 . Vasquez and colleagues 99, 100 found the mutation motif [(A|T|G|C)(T|C) C (A|T|C)]) is enriched in several cancers. Experimentally, they found that guanines in the complementary sequence context have a higher potential to trap electrons and thus have an increased chance of chemical modification.…”
Section: Hypermutation By Increase In Lesions or By Decrease In Errormentioning
confidence: 99%
See 1 more Smart Citation
“…Highly mutagenic 8-oxo-7,8 dihydroguanine (8-oxoG) could be the reason for such a bias, however other products of reactions of guanine and cytosine could also contribute 94 . Vasquez and colleagues 99, 100 found the mutation motif [(A|T|G|C)(T|C) C (A|T|C)]) is enriched in several cancers. Experimentally, they found that guanines in the complementary sequence context have a higher potential to trap electrons and thus have an increased chance of chemical modification.…”
Section: Hypermutation By Increase In Lesions or By Decrease In Errormentioning
confidence: 99%
“…Examples listed in TAB. 2 and below (see also 99, 147 ) can be used to illustrate these lines of analysis.…”
Section: Box1: Merging Statistical Pattern Analysis With Mechanistic mentioning
confidence: 99%
“…Several prominent mutation signatures consisting of mutated nucleotide and immediate (1–2 nucleotides) surrounding context (reviewed in (5; 10; 53; 94; 106)) have been identified. Another striking pattern of mutagenesis revealed by genome-wide sequencing of multiple samples of several cancer types was the presence of many mutation clusters (up to several hundred per sample, see Table 1; also reviewed in (104; 105)), identified by two independent and complementary analytical methods.…”
Section: The Phenomenology Of Mutation Clusters In Cancersmentioning
confidence: 99%
“…S1). However, our sample size was small and a more detailed analysis with more replicates will be necessary to conclusively elucidate the mutation spectrum at T C T. Interestingly, a markedly elevated mutation rate at T C T has also been reported in cancer genomes with proofreading-deficient Pol ε264142. The proofreading-deficient human Pol ε exhibits a preference for T C T to T A T transversions in vitro 26, and thus the deamination of me 5 C does not appear to be involved in the elevated mutation rate in tumours.…”
Section: Discussionmentioning
confidence: 93%